OPERATING GUIDELINES for the Sustainable Development Working Group. - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2001)
OPERATING GUIDELINES for the Sustainable Development Working Group adopted by the Sustainable Development Working Group on April 5th 2001 pending approval by the Senior Arctic Officials (SAOs). The activities of the Sustainable Development Working Group are governed by the Rules of Procedure of the Arctic Council. In undertaking its work, the Sustainable Development Working Group will also adhere to the Arctic Council Terms of Reference for the Sustainable Development Program, the Sustainable Development Framework Document, and other policies and directions provided by the Arctic Council Ministers. The following guidelines should be read in conjunction with the Rules of Procedure of the Arctic Council.